Beth's theorem and deflationism - Reply to bays - Ketland, J (2009)
Is the restricted, consistent, version of the T-scheme sufficient for an 'implicit definition' of truth? In a sense, the answer is yes (Haack 1978, Quine 1953). Section 4 of Ketland 1999 mentions this but gives a result saying that the T-scheme does not implicitly define truth in the stronger sense relevant for Beth's Definability Theorem. This insinuates that the T-scheme fares worse than the compositional truth theory as an implicit definition. However, the insinuation is mistaken. For, as Bays rightly points out, the result given extends to the compositional truth theory also. So, as regards implicit definability, both kinds of truth theory are equivalent. Some further discussion of this topic is mentioned (Gupta 2008, Ketland 2003, McGee 1991), all in agreement with Bays's analysis. © 2009 Ketland.